HISTOPATOLOGI AORTA TORASIKA TIKUS PUTIH (Rattus norvegicus strain wistar) JANTAN SETELAH PEMBERIAN DIET ATEROGENIK SELAMA 12 MINGGU - Sutrisno Tambunan; Zulkifli Malik; Ismawati " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Atherosclerosis is a chronic inflammatory disease caused by lipid deposition in arterial wall. Atherosclerosis could be induced in animal model (Rattus norvegicus) by feeding atherogenic diet. The objective of this research is to know the differences of histopathologic image between thoracic aorta of male white rat (Rattus norvegicus strain wistar) fed with standard diet and fed with atherogenic diet for 12 weeks. This research was an experimental laboratory with a post test only design. Twelve male rats were segregated into two groups (n=6) there were labelled as control group fed a standard diet and labelled as atherogenic group fed vitamin D3 and atherogenic diet which contain cholic acid 0,2%, fat 5% and yolk 2%. The experiment was designed for 12 weeks. The parameter used is atherosclerosis lesion score of all groups labelled. The result show that in atherogenic group there are macrophage, foam cell and intracellular lipid accumulation with 100% percentage, extracellular lipid accumulation 33,33% (for a little extracellular lipid), 66,66 (a lot of extracellular lipid) and surface defect with 0,16% while in control group there are macrophage, foam cell and intracellular lipid accumulation with 33,33% percentage. The statistic of Mann-Whitney test result shows (p=0,003). The conclusion that there is significant difference of histopathologic image between thoracic aorta of male white rat (Rattus norvegicus strain wistar) fed with atherogenic diet and fed with standard diet for 12 weeks.Keywords : thoracic aorta, atherosclerosis, atherogenic diet, histopathology.